Biaxial cyclic plasticity experiments and application of a constitutive model for cyclically stable material behaviour. (February 2016) - Madrigal, C.; Navarro, A.; Chaves, V.
Highlights: Describes tension–torsion cyclic plasticity experiments on AISI 4140 steel. Considers proportional, 90° out-of-phase and more complex strain histories. Shows application of a constitutive model for cyclically stable material behaviour. Model parameters derived from cyclic uniaxial tension and torsion tests. Abstract: An extensive experimental program was conducted on AISI 4140 steel under cyclic proportional and non-proportional biaxial strain histories. The application of a plasticity model for cyclically stable material behaviour based on the idea of distance in stress space is described. A detailed explanation is provided of the methodology to derive from the experimental data the metric coefficients needed for calculating distances and the hardening modulus function required in the flow equations. The model gives accurate results for the cyclic stress–strain curves obtained in proportional strain tests. It also calculates correctly the stabilized stress values in 90° out-of-phase experiments. For more complicated non-proportional cyclic strain paths, the stresses calculated with the model reproduce strikingly well the qualitative evolution of the experimental response. The quantitative agreement is also good, but obviously not as good as for the simpler strain histories.